Citizen Jurnalism Dalam Introduksi Potensi Pariwisata Halal di Pulau Madura - Oktavia Putri, Salsabila Nur; Rakhmawati, Yuliana (Jurnal Ilmu Komunikasi, 2024)
Bangkalan Regency, known as the city of santri and sholawat. Therefore, the slogan makes Bangkalan City has the potential for halal tourism. Citizen Journalism Tourism in Introducing Halal Tourism Potential in Bangkalan introduces halal tourism in Bangkalan Regency in the form of creative content on social media platforms. The purpose of this study is to analyze the role of citizen journalism's creative strategies in introducing halal tourism destinations to attract audiences to visit tourism destinations in Bangkalan Regency. The research method uses a qualitative descriptive research type. Using a phenomenological approach and collecting data using observations, interviews and documentation with informants. The results of the analysis and discussion show that Citizen journalism tourism in the introduction of halal tourism potential in Bangkalan Regency has an important role for tourism development.